Efektivitas Metode Read Aloud Terhadap Kemampuan Berpikir Kritis Anak Usia 5-6 Tahun - Yayu Fauziah; Purwati Purwati; Alfian Azhar Yamin (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aimed to determine the effectiveness of the read-aloud method in enhancing the critical thinking skills of children aged 5–6 years at PGRI Kedunghalang Kindergarten, Tasikmalaya Regency. A quasi-experimental research method with a non-equivalent control group design was employed. The research subjects comprised two groups: Class B2 as the experimental group (n = 10) and Class B1 as the control group (n = 10). Data collection was conducted through structured observation using 12 behavioral indicators adapted from Robert Ennis's dimensions of critical thinking. Data analysis involved descriptive statistics, the Normalized Gain (N-Gain) test, and parametric inferential statistics (Independent Sample t-Test) following the fulfillment of normality and homogeneity test prerequisites. Descriptive analysis results showed an increase in the experimental group's mean score from 24.0 to 39.3, while the control group's score rose from 21.2 to 28.9. The N-Gain test confirmed that the experimental group achieved an improvement efficiency index of 63% (moderate category), representing a significantly higher gain compared to the control group, which achieved only 28% (low category). Furthermore, the Independent Sample t-Test results indicated a significant difference in critical thinking skills between the two groups (sig. < 0.05). It is concluded that the read-aloud method, combined with dialogic scaffolding, is highly effective in stimulating the foundations of higher-order thinking skills in early childhood, as opposed to conventional, one-way teaching methods